Organocatalytic synthesis of 5‐hydroxyisoxazolidine catalyzed by camphor sulfonyl hydrazines through aza‐Michael addition/cyclization. Issue 3 (20th January 2020) - Xu, Fang‐Fang; Chen, Ling‐Yan; Sun, Peng; Lv, Yixin; Zhang, Yan‐Xue; Li, Jia‐Yu; Yin, Xiaoying; Li, Ya
Abstract: A series of chiral 5‐hydroxy isoxazolidines has been successfully synthesized through camphor sulfonyl hydrazine‐catalyzed asymmetric aza‐Michael addition reaction between N, O ‐protected hydroxyamines and enals. Moderate yields with moderate to good enantioselectivities (up to 96% enantiomeric excess [ee]) were achieved. It provides an alternative asymmetric approach to preparing isoxazolidine derivatives. Abstract :